2022
DOI: 10.1021/acs.jpcb.2c01295
|View full text |Cite
|
Sign up to set email alerts
|

Different Binding Modes of SARS-CoV-1 and SARS-CoV-2 Fusion Peptides to Cell Membranes: The Influence of Peptide Helix Length

Abstract: Although the amino acid sequences of SARS-CoV-1 and SARS-CoV-2 fusion peptides (FPs) are highly conserved, the cryo-electron microscopy structures of the SARS-CoV-1 and SARS-CoV-2 spike proteins show that the helix length of SARS-CoV-1 FP is longer than that of SARS-CoV-2 FP. In this work, we simulated the membrane-binding models of SARS-CoV-1 and SARS-CoV-2 FPs and compared the binding modes of the FPs with the POPC/POPE/cholesterol bilayer membrane. Our simulation results show that the SARS-CoV-2 FP binds to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
2
12
1
Order By: Relevance
“…In addition, our CAVS simulations show that the stable helical structure enables the hydrophobic residues to interact strongly with cholesterol, which endows the FP-L with a higher membrane-binding strength than the FP-S. This observation is consistent with the previous all-atom MD simulation results. , Finally, we investigated the effect of the disulfide bond between Cys840 and Cys851 on the membrane binding of the FP-L, finding that the disulfide bridge stabilizes the helical structure, which should strengthen the binding between the FP-L and the bilayer membrane.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, our CAVS simulations show that the stable helical structure enables the hydrophobic residues to interact strongly with cholesterol, which endows the FP-L with a higher membrane-binding strength than the FP-S. This observation is consistent with the previous all-atom MD simulation results. , Finally, we investigated the effect of the disulfide bond between Cys840 and Cys851 on the membrane binding of the FP-L, finding that the disulfide bridge stabilizes the helical structure, which should strengthen the binding between the FP-L and the bilayer membrane.…”
Section: Introductionsupporting
confidence: 89%
“…This observation is consistent with the previous all-atom MD simulation results. 31 , 64 Finally, we investigated the effect of the disulfide bond between Cys840 and Cys851 on the membrane binding of the FP-L, finding that the disulfide bridge stabilizes the helical structure, which should strengthen the binding between the FP-L and the bilayer membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Although the amino acid sequences of both FPs are quite similar ( Fig. 2 C), the corresponding cryo-electron microscopy structures show that the helix length of SARS-CoV FP is longer than that of the SARS-CoV-2 FP [36] . The higher hydrophobicity of the SARS-CoV-2 FP may also contribute to disrupting the target cell membrane [37] .…”
Section: Resultsmentioning
confidence: 93%
“…Importantly, the increase in membrane flexibility is more pronounced in the more rigid, Lo plasma membrane regions rich in cholesterol [35] . Shen et al [36] have recently compared the binding modes of SARS-CoV and SARS-CoV-2 FPs using in silico molecular dynamics. They showed that SARS-CoV-2 FP binds to a synthetic POPC/POPE/cholesterol bilayer membrane more effectively than the SARS-CoV FP [36] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation